Fault-tolerant control-based flexible AGV transportation in a seat assembly system. Issue 10 (2019) - Witczak, Marcin; Lipiec, Bogdan; Banaszak, Zbigniew
Abstract: The cyclic nature of the production flow enables just-in-time planning and organization of the associated supply chains. In turn, disruptions in the operation of machinery and equipment, which occur in practice, lead to deviations from nominal operation times. That lead to changes in production takt time, making it necessary to adjust previously created schedules for delivery/reception of materials. Consequently since a control action should be taken to adjust transport operation times within a specified time range, the following problem of fault-tolerant cyclic scheduling boils down to the dual stage task composed of linear- and mixed-linear-integer programming. Its advantage is that it can compensate the effects of certain faults such as delays present in the assembly station or reduced velocities of mobile robots enabling the system to return to the previously scheduled delivery times.